The Use of Herbal Preparations of Sour Turmeric and Betel Leaf on the Duration of Accelerated Healing in Adolescent Girls Who Experience Recurrent Vaginal Discharge in Palembang - Tetin Rismayanti; Dewi Ratna Sari; Delta Shafira; Nara Syawalla Rafelia; Nur Aisyah Humairoh; Siti Rahma Yunita Sari (Postgraduate, University of Mataram, 2025)
Recurrent vaginal discharge is a common problem among adolescent girls and may cause discomfort and affect daily activities. Herbal preparations such as sour turmeric (Curcuma xanthorrhiza) and betel leaf (Piper betle L.) are known for their antibacterial and anti-inflammatory properties that may accelerate the healing process. This study aimed to compare the effectiveness of sour turmeric and betel leaf herbal preparations in accelerating the healing duration of recurrent vaginal discharge among adolescent girls in Palembang in 2024. This experimental study used a two-group post-test-only design. The independent variable was the type of herbal preparation (sour turmeric and betel leaf), while the dependent variable was the duration of accelerated healing. The sample consisted of junior high school and Islamic boarding school students who experienced recurrent physiological vaginal discharge. Data were analyzed using the independent t-test with a significance level of 0.05. The findings showed a significant difference in healing duration between the two groups (p < 0.05). The betel leaf group experienced a faster recovery, with an average healing time 2.3 days shorter than the sour turmeric group. Betel leaf herbal preparation was more effective in accelerating the healing of recurrent vaginal discharge compared to sour turmeric. It is recommended for women as a natural alternative therapy for managing vaginal discharge.